Sino-Indian Rivalry and Security of Small States: The Case of Bangladesh - Haque, Mohd Amdadul; Hasan, Md. Navid (Academia Journal of Humanities & Social Sciences, 2025)
Bangladesh faces significant geopolitical challenges in maintaining strategic relationships with both China and India. The study deals with three pertinent questions: What is the nature of the relationship between India and China? Which underlying factors are most likely to escalate the rivalry in the near future? How does Bangladesh navigate this rivalry? The research analyses how the rivalry affects Bangladesh’s foreign policy and security strategy employing secondary sources of data. Employing Blainey’s model of the causes of war, it identifies seven factors that could fuel future conflict between China and India, using Moniruzzaman’s framework on the security of small states to assess Bangladesh’s strategic options. The paper concludes that Bangladesh’s best option for safeguarding its security is non-alignment, avoiding direct involvement in the rivalry while preserving its national interests. Bangladesh should pursue a non-aligned foreign policy to maintain its security and influence in the region, given the potential risks of involvement in the India-China rivalry.